U-PB ZIRCON DATING OF ROCKS OF THE PLATINIFEROUS FEDOROVA-PANA LAYERED MASSIF, KOLA PENINSULA - Nitkina E.A. (My University, 2006)
The Fedorova–Pana Massif (~400 km2 in area) located in the central Kola Peninsula belongs to the Northern belt of pyroxenite–gabbronorite PGE-bearing intrusions. The massif is confined to the junction of the Archean Keivy and Kola–Norwegian blocks in the north and Early Proterozoic Imandra–Varzuga structure in the south [3]. The Fedorova–Pana Massif incorporates the Fedorova, Lastjavr, Western Pana, and Eastern Pana blocks. The three latter blocks include “stratigraphic” (taxitic gabbronorite, norite, gabbronorite–gabbro) zones [4] with the ore-bearing Upper (ULH) and Lower (LLH) layered horizons.
Keywords: Fedorova–Pana massif; Kola peninsula